Enhancing Civil Servant Performance Through Digital Literacy and Organizational Adaptability - Syahrir; Rida Anjani; Zulaikha Rumaisha Alwi (PROCURATIO: Jurnal Manajemen & Bisnis, 2025)
Purpose – This study aims to examine how digital literacy and organizational adaptability jointly influence civil servant performance within the context of Indonesia’s digital transformation agenda. While digital tools are increasingly integrated into public sector operations, limited attention has been paid to the interaction between individual digital competencies and institutional adaptability in determining work effectiveness. This research contributes to a more comprehensive understanding of civil servant performance by addressing this interdependence. Design/method/approach – A qualitative exploratory case study approach was employed, involving semi-structured interviews with 12 civil servants from two government institutions—one at the national level and one at the regional level. The participants were selected purposively based on their active involvement in digital administrative processes. Thematic analysis was conducted to identify patterns related to digital skill application, organizational support, and performance outcomes. Findings – The findings indicate that digital literacy enhances civil servants’ efficiency, confidence, and engagement, but its impact is highly contingent upon the organizational environment. Adaptive institutions that promote learning, flexibility, and supportive leadership enable civil servants to fully utilize their digital competencies. In contrast, rigid bureaucracies with limited innovation capacity tend to inhibit performance, even among digitally skilled employees. The interplay between individual and organizational factors emerges as a critical determinant of effective public service delivery. Implications – The study provides practical insights for policymakers and public managers seeking to improve civil service performance. It recommends integrated capacity-building strategies that simultaneously enhance digital skills and foster adaptive institutional cultures. Theoretically, it advances public administration literature by linking micro-level competencies with macro-level organizational dynamics. Novelty/Originality – This research offers original contributions by exploring the dual role of digital literacy and organizational adaptability in a developing country context, an area that remains underexplored. It bridges individual and institutional perspectives, offering a holistic lens on performance enhancement in the digital era